Treatment with Circular External Fixation of Bicondylar Tibial Fractures: Potential in Accurate Reduction and Efficacy on Functional Results - Lovisetti, Giovanni; Vulcano, Ettore; Bettella, Lorenzo; Tasarib, Rohoman; Tondolo, Tania; Sala, Francesco (The Journal of Knee Surgery, 2018)
Surgical reconstruction of bicondylar tibial fractures with external fixation relies on indirect fracture reduction that could affect anatomical restoration. The aim of the present study is to evaluate the radiographic and clinical outcomes of tibial bicondylar fractures treated with circular external fixation. A total of 20 bicondylar fractures of the proximal tibia in 20 patients treated with circular external fixation were included in the study. Two fractures were open. Mean clinical and radiographic follow-up was 37.3 months after frame removal. Angular, translation, and length deformities were assessed on nonweight-bearing anteroposterior, lateral, and two 45 degrees oblique views. The medial proximal tibia (MPTA) and posterior proximal tibia angles (PPTA) were calculated in all cases. The condylar widening was calculated in relation to the width of the femoral condyles. Joint depressions or gaps of the articular surface were identified on the four views of the knee. The modified Hospital for Special Surgery (HSS) knee scoring system was used for clinical evaluation. The MPTA was good in 18 (90%) and fair in 2 patients (10%). The PPTA was good in 13 (65%), fair in 6 (30%), and poor in 1 patient (5%). The articular reduction was good in 12 (60%) and fair in 8 patients (40%). The condylar widening was good in 15 (75%) and fair in 5 patients (25%). Mechanical axis deviation was within the normal range in 11/12 patients (91.7%). All fractures consolidated. One deep infection was successfully treated with local debridement, the mean modified HSS knee score at the latest follow-up was 90.5 (range: 67–100). Articular reconstruction and tibia alignment based on radiographic evaluation in the present study, along with functional results compare favorably with those of external and internal fixation presented in the literature.
Keywords: Schatzker; tibial plateau; external fixation; radiographic alignment; knee X-ray